Cache replication for information-centric networks through programmable networks. (9th August 2019) - Nascimento, Erick Barros; Moreno, Edward David; Macedo, Douglas Dyllon Jeronimo De
Software-Defined Networking (SDN) is a new approach that decouples control from the data transfer function and can be directly programmable by the programming language. At the same time, Information-Centric Networks (ICNs) influence the search for information through network caching and multipart communication. Moreover, these projects are developed to solve traffic problems and have content transfer through a scalable network structure with simple management. The SDN covers ICNs, besides decoupling the control to allow flexibility of network settings to reduce overhead of segments. Based on this information, an architecture was designed to provide reliable content that can be replicated in the network. The ICN architecture proposed stores information through a logical volume to the next access, enabling connection with remote controllers for reliable storage in cloud environments. The cache efficiency achieved almost 50% reduction of time response, in addition, there was improvement around 10% when the number of parallel requests was increased.